Thermal analysis of conductive blends of PVDF and poly(o-methoxyaniline) - Malmonge, L. F. [UNESP]; Mattoso, L. H C (Elsevier, 2000)
The thermal behavior of blends of poly(vinylidene fluoride), or PVDF, and poly(o-methoxyaniline) doped with toluene sulfonic acid was studied by thermogravimetic analysis, electrical conductivity measurements, differential scanning calorimetry, X-ray diffraction and scanning electron microscopy. Blends with thermal and electrical conductivity stabler than the conductive polymer alone were obtained. Nevertheless, degradation occurs after a long period of time (500 h) at high temperatures. The possible association of the conductivity decay with dopant loss, degradation and structural and morphological changes of the blend is discussed. (C) 2000 Elsevier Science Ltd.

The thermal behavior of blends of poly(vinylidene fluoride), or PVDF, and poly(o-methoxyaniline) doped with toluene sulfonic acid was studied by thermogravimetic analysis, electrical conductivity measurements, differential scanning calorimetry, X-ray diffraction and scanning electron microscopy. Blends with thermal and electrical conductivity stabler than the conductive polymer alone were obtained. Nevertheless, degradation occurs after a long period of time (500 h) at high temperatures. The possible association of the conductivity decay with dopant loss, degradation and structural and morphological changes of the blend is discussed.
Keywords: Blends; Conducting polymers; Polyanilines; Conductive plastics; Differential scanning calorimetry; Electric conductivity measurement; Fluorine containing polymers; Morphology; Scanning electron microscopy; Thermal conductivity of solids; Thermogravimetric analysis; Vinyl resins; X ray diffraction analysis; Polymethoxyaniline; Polyvinylidene fluoride; Sulfonic acid; Polymer blends; aniline derivative; polymer; sulfonic acid derivative; toluene derivative; vinylidene fluoride; chemical structure; degradation; differential scanning calorimetry; electric conductivity; high temperature; molecular stability; polymerization; scanning electron microscopy; thermal analysis; thermogravimetry; X ray diffraction; blending; calorimetry; electrical conductivity; thermal conductivity; X-ray analysis